Aplikasi Wingeom dan Camtasia Studio untuk Pembuatan Media Pembelajaran Audio Visual - Nosa, Desta Evira; Farida, Farida (Desimal: Jurnal Matematika, 2018)
The purpose of this research is to produce the product in the form of audio-visual learning media using Wingeom and Camtasia Studio and to know the learner's response to audiovisual learning media using Wingeom and Camtasia Studio. This research uses research and development method. Learning media development procedure is done through several stages: (1) Analysis in the form of curriculum analysis, characteristic analysis of learners and technology analysis. (2) Design  in the form in the media and the preparation of instruments. (3) Development in the form of media creation process until media validation. (4) Implementation in the form of product testing to learners. (5) Evaluation. This research produces a mathematics learning media that has been declared valid and suitable to be used as a medium of mathematics learning by material experts, media experts, and linguists. From the results of validation by experts, then obtained average percentage of 91% with very good criteria. In the test results the average learner responded well with a percentage of 86%. So it can be concluded that the resulting audiovisual media is considered feasible to be used as a medium of learning mathematics.